Business models at the bottom of the pyramid: Leveraging context in undeveloped markets. (February 2017) - Ladd, Ted
Social enterprises serve distributed electricity to the bottom of the world's economic pyramid (BoP), where 4 billion people live on less than US2 per day and 1.6 billion lack access to electricity. Current mainstream theories of business models do not fully explain the logic by which these ventures create and capture value. Through interviews with 30 practicing entrepreneurs selling distributed electricity directly to rural BoP consumers, we employ grounded theory to derive a new framework of business models for the BoP that embeds the venture's offering into the context of the marketplace, including the consumer's social network, daily habits, mental models, and product constellations. This framework also incorporates affordability and the influences of government regulation. With further research, several of the concepts proposed in this framework might also apply to business models in other BoP sectors and in developed, mature, competitive markets.